Endoscopic and Histologic Predictors of Outcomes in Pediatric Ulcerative Colitis—Caveat Emptor - Stallard, Lorraine; Hussey, Séamus (Frontiers in Pediatrics, 2021)
Ulcerative colitis is a chronic, relapsing and remitting disorder that is heterogenous in its age of onset, extent and severity. Approximately 25% of all inflammatory bowel disease (IBD) is diagnosed during childhood. Paediatric IBD has the potential to follow a more aggressive disease course than adult phenotypes, including a higher risk for developing acute severe colitis and more extensive disease at diagnosis. The ability to predict disease course allows for stratification of patients and treatment options so that therapies can be tailored to the individual. The timing of endoscopy and biopsy at diagnosis and follow up may influence short- and long-term predictive factors. To date, many different potential predictive markers have been suggested including clinical disease severity, disease extent, serum albumin, faecal calprotectin and genetic polymorphisms. Endoscopic and histological scoring indices, disease classification systems, advanced endoscopy modalities and individual histological features have shown potential predictive capabilities. Furthermore, the importance of mucosal healing, whether endoscopic or histological healing, is an emerging treatment goal. In this review we will focus on the endoscopic and histological predictive factors in paediatric UC and the areas needing future study in this field.